PIN28 Comparative Effectiveness of Triple Therapy Versus Dual Therapy for Chronic Hepatitis C Virus Infection in Kazakhstan - Almadiyeva, A.; Kostyuk, A.; Nurgozhin, T. (My University, 2013)
Currently, 23 thousand people (registered) are suffering from Hepatitis C in Germany (more 60% genotype 1). TThe licensing of direct-acting antivirals heralds a new era in the treatment of hepatitis C virus (HCV) genotype 1. Clinical studies showed a significant increase in sustained virological response rates from 38-46% to 63-79%. This study was to evaluate the cost-effectiveness of newly introduced triple therapy with Telaprevir (TVR+PR) compared to dual therapy (PR) for the treatment of genotype 1 hepatitis C virus (HCV) infection in previously untreated patients.